Salivary IL-8, IL-6 and TNF-α as Potential Diagnostic Biomarkers for Oral Cancer - Haafsa Arshad Sahibzada; Zohaib Khurshid; Rabia Sannam Khan; Mustafa Naseem; Khalid Mahmood Siddique; Maria Mali; Muhammad Sohail Zafar (Diagnostics, 2017)
Saliva has been useful as a liquid biopsy for the diagnosis of various oral or systemic diseases, and oral squamous cell carcinoma (OSCC) is no exception. While its early detection and prevention is important, salivary cytokines expression, specifically of Interleukin-8 (IL-8), Interleukin-6 (IL-6) and Tumor necrosis factor (TNF-α), does contribute to the pathogenesis of cancer and these cytokines serve as potential biomarkers. Their excessive production plays a role in cancer progression and establishment of angiogenesis. However, other inflammatory or immunological conditions may affect the levels of cytokines in saliva. This article reviews the expression of levels of specific cytokines i.e., IL-8, IL-6 and TNF-α, their signaling pathways in the development of oral cancer, and how they are essential for the diagnosis of OSCC and updates related to it. Apart from serum, the saliva-based test can be a cost-effective tool in the follow-up and diagnosis of OSCC. Moreover, large-scale investigations are still needed for the validation of salivary cytokines.